The Effect of Scaffolding Prompting Questions on Scientific Writing Skills in the Inquiry Classroom - Supeno; Maryani; Lesmono, Albertus Djoko; Astutik, Sri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Scientific writing is an essential skill as an indicator to determine the ability to analyze and reflect on the results of thinking. However, students often experience difficulties in developing writing skills. This study tried a solution by applying inquiry learning by assisting with scaffolding prompting questions. The aims of this study is to analyze the effect of the scaffolding prompting questions in guided inquiry learning on scientific writing skills. The type of this research is a quasi-experiment conducted in senior high school. Science learning is conducted in two classes; experiment and control class with different treatments. The experiment class implemented guided inquiry learning assisted by a scaffolding prompting question, while the control class was taught with guided inquiry learning without scaffolding. Scientific writing skills are obtained from the evaluation of practicum reports that students have done after being trained for three lessons. The results of statistical tests on scientific writing skills using the independent sample t-test showed that the scientific writing skills of the experimental class students differed from the control class. Then, it can be concluded that the scaffolding prompting question in guided inquiry learning significantly influences scientific writing skills.